Fast method of speckle suppression for reflection phase microscopy - Stremplewski, Patrycjusz; Nowakowski, Maciej; Borycki, Dawid; Wojtkowski, Maciej (Photonics Letters of Poland, 2018)
Light propagating in turbid medium is randomly altered by optical inhomogeneities, which not only change the momentum and polarization of light but also generate a speckle pattern. All these effects strongly limit capabilities of laser based, quantitative phase–sensitive optical biomedical imaging modalities by hindering a reconstruction of phase distribution. Here we introduce the method of rapid incident light modulation, which allows to suppress speckle noise and preserve the spatial phase distribution. We implement this approach in the full-field Michelson interferometer, where the incident light is modulated using the digitalmicromirror device (DMD). Full Text: PDF References F. Zernike, "Phase contrast, a new method for the microscopic observation of transparent objects part II," Physica 9, 974-986 (1942). CrossRef M. C. Pitter, C. W. See, and M. G. Somekh, "Full-field heterodyne interference microscope with spatially incoherent illumination," Opt. Lett. 29, 1200-1202 (2004). CrossRef N. B. E. Sawyer, S. P. Morgan, M. G. Somekh, C. W. See, X. F. Cao, B. Y. Shekunov, and E. Astrakharchik, "Wide field amplitude and phase confocal microscope with parallel phase stepping," Review of Scientific Instruments 72, 3793-3801 (2001). CrossRef G. W. John and I. H. Keith, "A diffuser-based optical sectioning fluorescence microscope," Measurement Science and Technology 24, 125404 (2013). CrossRef S. Lowenthal and D. Joyeux, "Speckle Removal by a Slowly Moving Diffuser Associated with a Motionless Diffuser," J. Opt. Soc. Am. 61, 847-851 (1971). CrossRef S. Kubota and J. W. Goodman, "Very efficient speckle contrast reduction realized by moving diffuser device," Applied Optics 49, 4385-4391 (2010). CrossRef Y. Li, H. Lee, and E. Wolf, "The effect of a moving diffuser on a random electromagnetic beam," Journal of Modern Optics 52, 791-796 (2005). CrossRef C.-Y. Chen, W.-C. Su, C.-H. Lin, M.-D. Ke, Q.-L. Deng, and K.-Y. Chiu, "Reduction of speckles and distortion in projection system by using a rotating diffuser," Optical Review 19, 440-443 (2012). CrossRef J. Lehtolahti, M. Kuittinen, J. Turunen, and J. Tervo, "Coherence modulation by deterministic rotating diffusers," Opt. Express 23, 10453-10466 (2015). CrossRef J.-W. Pan and C.-H. Shih, "Speckle reduction and maintaining contrast in a LASER pico-projector using a vibrating symmetric diffuser," Opt. Express 22, 6464-6477 (2014). CrossRef J. I. Trisnadi, "Hadamard speckle contrast reduction," Optics Letters 29, 11-13 (2004). CrossRef M. Szkulmowski, I. Gorczynska, D. Szlag, M. Sylwestrzak, A. Kowalczyk, and M. Wojtkowski, "Efficient reduction of speckle noise in Optical Coherence Tomography," Opt. Express 20, 1337-1359 (2012). CrossRef J. W. Goodman, Speckle phenomena in optics: theory and applications (Roberts and Company Publishers, 2006). DirectLink Y. Choi, P. Hosseini, W. Choi, R. R. Dasari, P. T. C. So, and Z. Yaqoob, "Dynamic speckle illumination wide-field reflection phase microscopy," Opt. Lett. 39, 6062-6065 (2014). CrossRef Y. Choi, T. D. Yang, K. J. Lee, and W. Choi, "Full-field and single-shot quantitative phase microscopy using dynamic speckle illumination," Opt. Lett. 36, 2465-2467 (2011). CrossRef R. Zhou, D. Jin, P. Hosseini, V. R. Singh, Y.-h. Kim, C. Kuang, R. R. Dasari, Z. Yaqoob, and P. T. C. So, "Modeling the depth-sectioning effect in reflection-mode dynamic speckle-field interferometric microscopy," Optics Express 25, 130-143 (2017). CrossRef M. Schmitz, T. Rothe, and A. Kienle, "Evaluation of a spectrally resolved scattering microscope," Biomedical optics express 2, 2665-2678 (2011). CrossRef P. Judy, The line spread function and modulation transfer function of a computer tomography scanner, Med. Phys (1976), Vol. 3, pp. 233-236. CrossRef